How to Mastery Arabic Vocabularies by Using Memorization Method and Visual Learning - An Nury, Ahmad Husein; Muh. Naim Madjid (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Abstract This study examines the mastery of Arabic vocabulary among students of Islamic junior high school An-Nur in Bengkalis, Riau, Indonesia, which focus on the utilizing of memorization method and visual learning by using Canva application. The goal of this study is to introduce and implement directly the Arabic vocabularies about daily activities through both methods, memorization and visual learning, in the classroom and the students are encouraged to involve actively. The sample of this research is 48 students for three classes that were selected by using Saturation Sampling, is sampling approach that involves all members of the population. There are four methods for collecting data are observation, interview, questionnaire, and documentation. To highlight the efficiency of used method, the researcher conducted an evaluation (Post-test) which was given to students after the teacher explained and practiced both methods, memorization and visual learning, in front of all respondents. Descriptive analysis approach was utilized in this qualitative research, which was based on the assumption that selecting controlled samples would generate trustworthy feedback. The research findings indicate that the efficacy of learning through modern media, such as Canva, surpasses the traditional approach of vocabulary memorization. This is evident from the assessment results, where the average score for class 7 by using Canva was 87, reflecting a 5-point improvement compared to the 82 achieved through the memorization method. Meanwhile, both methods yielded identical scores of 95 for class 8. In the case of class 9, Canva demonstrated a slight advantage with an average score of 96, surpassing the 95 obtained through the memorization method by one point. To sum up, the researcher strongly believes that visual learning by Canva is more effective to increase the student’s Arabic vocabularies because it more easier and interest for the students to remember the words.